Compassion focused therapy for complex posttraumatic stress disorder: A randomized controlled trial: Terapia centrada en la compasión para el trastorno de estrés postraumático complejo: Un ensayo controlado aleatorizado - Ríos-Mercado, Sara P.; Tena-Suck, Antonio; Lucio y Gómez Maqueo , María Emilia; Villafuerte-Montiel , Ana Lilia; Fuentes-Balderrama , Jaime (Revista de Psicopatología y Psicología Clínica, 2025)
ABSTRACT Objective: Compassion focused therapy (CFT) has been proposed for complex posttraumatic stress disorder (C-PTSD) due to its focus on shame and self-criticism. This study evaluated the efficacy of an individual CFT protocol specifically designed for CPTSD. Method: Forty-one participants meeting ICD-11 criteria for diagnosis of C-PTSD (N = 41, ranged 18-65 yrs old; 75.6% were female) were randomly assigned to receive 12-15 individual sessions of CFT or prolonged exposure (PE) via teletherapy. Participants were assessed at baseline, posttreatment, and six-month follow-up. Results: Repeated measures ANOVAs indicated significant time effects across all outcomes. Both CFT and PE produced reductions in posttraumatic symptoms, shame, self-criticism, depression, anxiety, stress, and dissociation, along with increases in self-compassion and self-soothing ability. PE was associated with decreased compassion for others at follow-up, whereas CFT demonstrated an increase in compassion from others. Treatment completion rates were higher for CFT (76.2%) than for PE (60%). Conclusions: Findings suggest CFT is effective for C-PTSD, offering comparable outcomes to PE with potentially greater tolerability. RESUMEN Objetivo: La terapia centrada en la compasión (CFT) ha sido propuesta para el trastorno de estrés postraumático complejo (TEPT-C) por su enfoque en la vergüenza y la autocrítica. Este estudio evaluó la eficacia de un protocolo individual de CFT diseñado para TEPT-C. Método: Un total de 41 participantes que cumplieron los criterios CIE-11 para el diagnóstico de TEPT-C (N = 41, con rango de edad entre 18 y 65 años; el 75.6% eran mujeres) fueron asignados aleatoriamente para recibir 12-15 sesiones de CFT o exposición prolongada (EP) mediante teleterapia. Los participantes fueron evaluaron en línea base, post-tratamiento y seguimiento a seis meses. Resultados: Los ANOVAs de medidas repetidas indicaron efectos significativos en todas las variables de resultado. Ambos tratamientos produjeron reducciones en síntomas postraumáticos, vergüenza, autocrítica, depresión, ansiedad, estrés y disociación, con aumentos en autocompasión y autotranquilización. La EP se asoció a menor compasión hacia otros en el seguimiento, mientras que la CFT aumentó la compasión recibida. Las tasas de finalización del tratamiento fueron superiores para la CFT (76.2%) que para la EP (60%). Conclusiones: La CFT es eficaz para el tratamiento del TEPT-C, con resultados comparables a la EP, y potencialmente posee mayor tolerabilidad.